Do leaders matter? International conflict, leader traits, and leader selection - Bognar, R (2023)
Why do leaders start conflicts? The bulk of IR tends to look outside of leaders, focusing on institutional and structural forces. Where there is more uncertainty is whether the factors within leaders might also influence their decision to start conflicts. Thus, this thesis asks the question: To what extent do the personal traits of leaders influence their decision to start international conflicts? Recent literature has found that several traits of leaders strongly predict conflict initiation, such as military experience and age. However, these findings may be biased if leaders with these traits are more likely to be selected into environments where the probability of conflict is greater. Yet, this problem of selection has not been given enough attention in previous research. To deal with the problem of selection, I develop a unique strategy, which I call the “counterfactual leader strategy.” The core idea of this strategy is that each time a leader is selected in reality, there is a counterfactual world in which someone else was selected instead. I call these individuals “counterfactual leaders” and the traits of these individual can be used as a “placebo” to indirectly test for bias. Since the counterfactual leaders' traits should not be associated with conflict initiation, any association reveals bias in the traits of leaders. Using an original dataset on leaders and counterfactual leaders between 1945 and 2004, I find that several traits of counterfactual leaders predict conflict in the same way as those traits among leaders. I argue this is because states that frequently engage in conflict are more likely to have candidates with these traits due to demographics and thus have a higher probability of selecting a leader with one, even if by chance. Therefore, I argue traits do not influence leaders’ decision to start conflicts, and what matters instead is the environment they are selected into.